Strategic Human Resource Management Practices and their reflections for Organizational Performance Improvement A Survey Study of the views of a sample of Managers Baghdad Soft Drinks company/ Zafaraniya - سعد خالد سلمان (Journal of Economics and Administrative Sciences, 2014)
The aims of research is to identify the role of strategic human resource management Practices in organizational performance improvement in the Baghdad soft drinks company, as well as the implications of the results for both managers and practitioners. In order to achieve the objectives of the research, the researcher designed questionnaire included (40) items to collect the initial data from the research sample consisting of (53) Single. In light of that has been collecting and analyzing data and test hypotheses using the statistical package for Social Sciences (SPSS21), and use a number of statistical methods to achieve the goal of the research, including the means, standard deviations and simple correlation and path analysis. After conducting an analysis of research data and hypotheses, research found a number of results most notably refers to: the level of strategic human resource management practices for managers have a field respondent was above average and to the strong influence of compensation strategy to improve organizational performance and lowest power in the employment strategy. The research found a number of conclusions was notably: The nature of work in Baghdad soft drinks company surveyed based on the need for strategic human resource management practices with the company surveyed, with appeared a correlation significant relatively strong among all human resources management strategies and organizational performance of the company surveyed, and this demonstrates the important role played by human resources management and strategies in promoting and supporting organizational performance. It was recommended by research need to work on developing a strategy and plan of private employment and adhere to the company’s management that enjoys these strategic flexibility and focus long-term, taking into account the issue of the diversity of experiences and skills and capacities of individual applicants for jobs, it is necessary to fit these strategy with the strategy of the organization.